2018
DOI: 10.1101/292151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An ultra-dense haploid genetic map for evaluating the highly fragmented genome assembly of Norway spruce(Picea abies)

Abstract: 27Norway spruce (Picea abies (L.) Karst.) is a conifer species of substanital 28 economic and ecological importance. In common with most conifers, the P. abies 29 genome is very large (~20 Gbp) and contains a high fraction of repetitive DNA. The 30 current P. abies genome assembly (v1.0) covers approximately 60% of the total 31 genome size but is highly fragmented, consisting of >10 million scaffolds. The 32 genome annotation contains 66,632 gene models that are at least partially validated 33 (www.congenie.or… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…These results represent the most complete and dense map ever built for the species [previous map had 3,856 markers in Westbrook et al. (2015)], and one of the few ultradense linkage maps available to date in gymnosperms (others include Norway spruce, Bernhardsson et al. 2019; and Ginkgo biloba , Liu et al.…”
Section: Resultsmentioning
confidence: 86%
“…These results represent the most complete and dense map ever built for the species [previous map had 3,856 markers in Westbrook et al. (2015)], and one of the few ultradense linkage maps available to date in gymnosperms (others include Norway spruce, Bernhardsson et al. 2019; and Ginkgo biloba , Liu et al.…”
Section: Resultsmentioning
confidence: 86%
“…Mapping to paralog sequences could also distort the distributions of quality scores. Instead of hard filtering based on arbitrary cutoffs, we applied a protocol of variant quality score recalibration, parameters of which were trained using set of SNPs discovered in a pedigree study (Baison et al, ; Bernhardsson et al, ). This should help reduce false‐positive discovery but may also bias toward shared SNPs and less private ones in P. obovata and P. omorika .…”
Section: Discussionmentioning
confidence: 99%
“…HaplotypeCaller was used for individual genotype identification, and joint SNP calling was performed across all samples using GenotypeGVCFs. We then applied the same variant quality score recalibration protocols as Baison et al (), which were trained on a set of ~21,000 SNPs identified from a pedigree study (Bernhardsson et al, ). This resulted in 2,406,289 SNPs after recalibration.…”
Section: Methodsmentioning
confidence: 99%
“…For the VQSR analysis two datasets were created, a training subset and an input file. The training dataset was derived from the Norway spruce genetic mapping population showing expected segregation patterns (Bernhardsson et al ., ) and assigned a prior value of 15.0. The input file was derived from the raw sequence data using gatk with the following parameters: extended probe coordinates by +100 excluding INDELS, excluding LowQual sites, and keeping only bi‐allelic sites.…”
Section: Methodsmentioning
confidence: 99%